RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE ABOUT COVID-19 AND IMPLEMENTATION OF MOVEMENT CONTROL ORDER (MCO) AMONG THE MEMBERS OF THE ALLIED HEALTH SCIENCE IN THE TRAINING INSTITUTE OF THE MINISTRY OF HEALTH MALAYSIA, KOTA KINABALU (ILKKM KK) - Baidi Baddiri; Mohd Khairuddin Abdullah @Jerry Abdullah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Safety and Healthcare system become the government’s main agenda, especially when the country is facing a critical global epidemic crisis, known as the transmission of the third wave of COVID-19. The transmission of COVID-19 wave with a very sharp increase in cases on October 12, 2020, where the number of cases was detected increase drastically compare to the first wave of epidemic compilation. The Country of Sabah is a state that reports so many cases of daily infections that up to 600 active cases are detected every day and subsequently places the state of Sabah become a red zone. This might be due to a lack of knowledge among the community, especially after the state election. Therefore, the emphasis on knowledge level is an important aspect in curbing the transmission of COVID-19. Thus, this study was conducted to find out what is the level of knowledge about COVID-19 and the Movement Control Order (MCO) as well as to identify the relationship between these two variables in breaking the chain of COVID-19 transmission, especially among the ILKKM KK staff. The study design was applying quantitatively in the research methodology, by the implementation of questionnaires through surveys, while sample randomize sampling was used as a sampling method with a total of 267 respondents consisting of ILKKM KK staff. Analysis of instrument evaluation and sampling methods is also discussed in this study. The results showed that the patient’s level of knowledge about COVID-19 was at a high level with a mean value = 3.902, SD = 0.423. However, the level of knowledge about MCO is at a moderate level with a mean value = 3.631, SD = 0.323. Meanwhile, correlation analysis showed there is a strong relationship between knowledge of COVID-19 and knowledge of MCO with correlation value r = 0.79, p> 0.05. Thus, the results of this analysis show that there is a strong relationship between the knowledge level of COVID-19 and MCO in deciding the chain of infection of COVID-19, especially among the ILKKM KK residents.